Inducible Resistance to β-Lactams in Oxacillin-Susceptible mecA1-Positive Staphylococcus sciuri Isolated From Retail Pork - Cai, Yifei; Zheng, Liangjun; Lu, Yao; Zhao, Xu; Sun, Yanting; Tang, Xingyuan; Xiao, Jinhe; Wang, Chen; Tong, Chao; Zhao, Lili; Xiao, Yingping; Zhao, Xin; et al. (Frontiers in Microbiology, 2021)
Most isolated strains of Staphylococcus sciuri contain mecA1, the evolutionary origin of mecA, but are sensitive to β-lactams (OS-MRSS, oxacillin-susceptible mecA1-positive S. sciuri). In order to improve the efficacy of antibiotic treatment, it is important to clarify whether the resistance of OS-MRSS to β-lactams is an inducible phenotype. In this study, three OS-MRSS strains with oxacillin MIC= 1 µg/mL were isolated from 29 retail pork samples. The resistance of OS-MRSS to β-lactams (MIC> 256 µg/mL) was found to be induced by oxacillin and the induced resistance was observed to remain stable within a certain period of time. Interestingly, the induced β-lactam resistance was not caused by mecA1, heterogeneous resistance or any genetic mutation, but mainly due to increased wall teichoic acid synthesis that thickened the cell wall. The induced strains also showed slower growth rate, as well as decreased adhesion ability and biofilm thickness. These phenotypes were found to be achieved through altered gene expression in associated pathways, such as citrate cycle and pentose phosphate pathway. The results challenge the traditional antibiotic sensitivity test. In the presence of β-lactam antibiotics, OS-MRSS that was initially sensitive to β-lactams was observed to gradually develop β-lactam resistance in several days. This often-neglected phenomenon in antibiotic sensitivity tests requires further research attention.